The Effectiveness of Group Guidance with Conflict Management Technique to Improve The Interpersonal Communication of Students (Jurnal Bimbingan Konseling, 2018)
This study aimed to determine the effectiveness of group guidance with conflict management technique on students’ interpersonal communication. The experimental design employed was in form of one-group pretest posttest design by involving 10 students. The results of Cohen d effectiveness test with the effectiveness measurement of 0.885 revealed the relatively high effectiveness found in the implementation of group guidance with conflict management technique to improve interpersonal communication. Meanwhile, based on the paired t-test, it was known that there was an increase in students’ interpersonal communication within the implementation of group guidance with conflict management technique (t(9) = 9.192, p < 0.01). According to the findings, the understanding of the mechanisms, knowledge and experience as well as interpersonal communication are the foundation to help students with conflict disorders and further allow for effective interventions. At last, the discussion of this study was focused on the possibility of the implementation of group guidance with conflict management technique to improve students’ interpersonal communication.